2010
DOI: 10.1097/hjh.0b013e32833a7de6
|View full text |Cite
|
Sign up to set email alerts
|

Increased arterial stiffness in nonalcoholic fatty liver disease: the Cardio-GOOSE study

Abstract: This study has shown a possible independent role of NAFLD in determining arterial stiffness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 48 publications
5
71
1
1
Order By: Relevance
“…28,29 Therefore, whether the increased cardiovascular risk in NAFLD patients is simply an epiphenomenon conferred by metabolic syndrome is still in debate. Our study, along with some others, 6,7 demonstrated that the strong correlation between atherosclerosis and NAFLD was independent of insulin resistance and metabolic syndrome. Meanwhile, subjects with both NAFLD and metabolic syndrome had remarkably higher levels of CIMT and ba-PWV compared with those with either of these diseases, which imply that the effect on atherosclerosis of NAFLD or metabolic syndrome might not fully overlap.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…28,29 Therefore, whether the increased cardiovascular risk in NAFLD patients is simply an epiphenomenon conferred by metabolic syndrome is still in debate. Our study, along with some others, 6,7 demonstrated that the strong correlation between atherosclerosis and NAFLD was independent of insulin resistance and metabolic syndrome. Meanwhile, subjects with both NAFLD and metabolic syndrome had remarkably higher levels of CIMT and ba-PWV compared with those with either of these diseases, which imply that the effect on atherosclerosis of NAFLD or metabolic syndrome might not fully overlap.…”
Section: Discussionsupporting
confidence: 83%
“…[5][6][7][8][9][10][11][12][13] In some relatively small samples from the community population, ultrasonographically diagnosed NAFLD has been found to be independently associated with carotid atherosclerosis and arterial stiffness. 6,7 Biopsy-proven NAFLD patients had remarkably greater carotid intimamedia thickness (CIMT) compared with that of age-, sex-, and body mass index (BMI)-matched healthy subjects in a case-control study. 8 Nevertheless, in another study including 101 patients with type 2 diabetes mellitus, NAFLD diagnosed by 1H-magnetic resonance spectroscopy is not associated with CIMT.…”
mentioning
confidence: 99%
“…It affects 20-35% of the general population in developed countries and its prevalence reaches 70-90% in subjects with obesity, MetS or T2DM [52]. NAFLD is considered the hepatic manifestation of MetS, since it is closely related to other clinical features of MetS [53,54]. Interestingly, AS appears to be independently associated with NAFLD [53,54].…”
Section: As In Mets-associated Nafldmentioning
confidence: 99%
“…NAFLD is considered the hepatic manifestation of MetS, since it is closely related to other clinical features of MetS [53,54]. Interestingly, AS appears to be independently associated with NAFLD [53,54]. Moreover, the results of a large study (n=4,467) suggested that not only the presence but also the severity of NAFLD are associated with AS in non-hypertensive, nondiabetic subjects with or without MetS [55].…”
Section: As In Mets-associated Nafldmentioning
confidence: 99%
“…9 Several factors, such as obesity, diabetes, metabolic syndrome, hypertension and dyslipidemia, are proven to be associated with arterial stiffness. 10 Although there is an insignificant association between NAFLD and arterial stiffness in hypertensive patients without additional cardiovascular risk factors, 11 studies have shown that NAFLD is positively related to arterial stiffness in general population [12][13][14] and adolescents. 15 Furthermore, a positive association of NAFLD with arterial stiffness was also found in non-hypertensive and nondiabetic subjects.…”
Section: Introductionmentioning
confidence: 99%